Concept of Time Travel and The Different Theories for Making It Possible and The Implications of Time Travelling - Younus, Muhammad; Nurmandi, Achmad; Suswanta, Suswanta (Journal of World Science, 2023)
The purpose of this paper is to explain in detail the concept of time travel, also how it was popularized, and lastly, the theories presented to make it possible and what impact it will have if time travel becomes possible soon. This research uses qualitative research type, evaluating data from qualitative research is "The VOSviewer" software. Time Travel is a concept that has long been a topic of great interest to the scientific community and the common people who see it on the big screen through interesting plots and visualizations in movies and series. So, everyone's thoughts on the concept of benefits can be different, but everyone is on the same page to welcome any possibility to make it happen. Time travel is interesting and in demand, it is necessary to continue to conduct research and development, the government must invest more, and we must be careful and cooperate as one community for its development and use.